1993
DOI: 10.1017/s0031182000074953
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the feeding behaviour of parasitic third-stage hookworm larvae

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…RNA was also isolated from 5,000 L3 that had been activated by incubating them in 50% fetal bovine serum for 2 h at 37°C. This process has been shown to induce feeding of hookworm L3 and upregulate the expression of selected genes (27)(28)(29)(30)(31)(32). The primers used for the RT-PCR corresponded to a 200-bp fragment of the AceKI cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was also isolated from 5,000 L3 that had been activated by incubating them in 50% fetal bovine serum for 2 h at 37°C. This process has been shown to induce feeding of hookworm L3 and upregulate the expression of selected genes (27)(28)(29)(30)(31)(32). The primers used for the RT-PCR corresponded to a 200-bp fragment of the AceKI cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from A. ceylanicum L3 cultured from the feces of infected hamsters (21,22), as well as from adult worms. Additional RNA was isolated from A. ceylanicum L3 that had been activated by incubation in 50% fetal calf serum, which has been shown to stimulate feeding of hookworm larvae and upregulate expression of certain genes (27)(28)(29)(30)(31)(32). As shown in Fig.…”
Section: Vol 72 2004 Hookworm Kunitz Inhibitor 2215mentioning
confidence: 99%
“…ceylanicum larvae (22,23) were generously provided by John Hawdon and Peter Hotez at The Yale University School of Medicine, and the parasite life cycle was maintained as described previously (24). Three-week-old Syrian hamsters (LVG strain) were infected orally by gavage with 100 -150 L 3 per animal.…”
Section: Hookworms--infective Third Stage (L 3 )mentioning
confidence: 99%
“…Blood loss resulting from A. ceylanicum infection can cause severe anemia. Eosinophilic enteritis is presumed to be an allergic response to hookworm secretions (Hawdon et al 1993;Hotez et al 1995;Harrop et al 1996). Infections with this nematode are very common in tropical regions, especially in Asia (Hotez et al 1995;Chan 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Proteinases of larval and adult stages of A. caninum, the closest relative of A. ceylanicum, have been extensively studied. Apart from cysteine proteinases, metalloproteinases (Dowd et al 1994;Hawdon et al 1993) and aspartic proteinases (Harrop et al 1995a, b;Brown et al 1999) have been found. By contrast, little is known about proteinases of A. ceylanicum and the role of these enzymes in host-parasite interactions.…”
Section: Introductionmentioning
confidence: 99%